A study on the competence of middle school mathematics teachers in Hebei province under the background of craftsmanship spirit - Liu, Xuhao; Wang, Jiali (Nurture, 2024)
Purpose: Excellent education is only possible with teachers who possess exceptional skills. This study is based on the competency characteristics of middle school mathematics teachers, constructs a teacher competency model that integrates the spirit of craftsmanship and identifies the professional qualities, motivations and attitudes that outstanding mathematics teachers possess. Design/Methodology/Approach: This study collected information and interview data from 12 experts through in-depth interviews and then encoded and summarized the themes through theme analysis to construct a competency system for high school mathematics teachers in Hebei Province. Thirty experts were given questionnaires to complete. The competency model was then validated and revised using the fuzzy Delphi method (FDM) and the relative importance of each indication was examined using the analytical hierarchy process (AHP). Findings: The fuzzy Delphi questionnaire shows that the expert consensus meets the requirements of the verification value while the analytic hierarchy process questionnaire shows that the expert opinions have passed the consistency test. Conclusion: This study integrates the spirit of craftsmanship with the competency characteristics of middle school mathematics teachers and constructs a teacher competency model. The constructed model was subjected to fuzzy Delphi validation and analytic hierarchy process weight analysis by distributing questionnaires. The conclusion verifies the reliability and validity of the established model. Contribution to the Literature: This study introduces the spirit of craftsmanship into the teacher competency model enriching the connotation and extension of teacher competency research. Interpreting teacher competency with craftsmanship traits can make the competency characteristics of teachers more concrete.